ANALISIS TEORI USES AND GRATIFICATION: MOTIF MENONTON KONTEN FIRMAN TUHAN INFLUENCER KRISTEN PADA MEDIA SOSIAL TIKTOK - Jeremia Engelita Wakas; Maria Barten Natalia Wulage (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
This study aims to understand the motives for watching Christian Influencer's Word of God content on TiktTok Social Media using Uses and Gratification Theory analysis. According to Katz, Gurevitch and Haas (1973), the motives in question are based on needs that are satisfied by the media, which are discussed in one of the theories of mass communication, namely Uses & Gratification Theory, such as cognitive, affective, personal integration, social integration and tension release needs. The research subject is the audience of Brian Siawarta's Word of God content on TikTok Social Media. The research method uses descriptive qualitative methods with data collection techniques through observation and interviews with two sources who are viewers of the Word of God content of Pastor Brian Siawarta on TikTok Social media. The results showed that the motive for watching God's Word content was driven by cognitive, affective, social integration and tension release needs. Meanwhile, the need for personal integration is not the main motive to increase the credibility and confidence of the audience but adds to the credibility of Brian Siawarta as an influencer. In the study, it was found that interpersonal communication exists between communicators with audiences and fellow audiences. It was also found that there are two types of TikTok social media users, namely 1) TikTok users only as viewers of other people's content; and 2) users as well as viewers who publish content for others to see, so these two things can affect a person's personal integration motives in choosing and watching TikTok content.